2009
DOI: 10.1002/app.30696
|View full text |Cite
|
Sign up to set email alerts
|

Improving the performance of urea‐formaldehyde wood adhesive system using dendritic poly(amidoamine)s and their corresponding half generations

Abstract: Full as well as half generations of dendritic poly(amido amine)s (PAMAMs) were introduced onto urea-formaldehyde (UF) wood adhesive system as modifiers to increase its stability and enhance the performance of the bonded wood joints with it. The effect of the modifiers on the physical properties and mechanical performance was discussed on the light of gel times, curing exotherms using differential scanning calorimetry (DSC), infra-red (IR), and shear strength measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 77 publications
0
30
0
Order By: Relevance
“…21,22 Amidation of the resulting esters in a subsequent step with ethylenediamine gives another subunits. Completion of this sequence leads to a full generation with amine terminals (Gn-NH 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…21,22 Amidation of the resulting esters in a subsequent step with ethylenediamine gives another subunits. Completion of this sequence leads to a full generation with amine terminals (Gn-NH 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In brief, this hyperbranched polymer, HB(MA-EDA)3, was not suitable for the modification of UF resins as particleboard binders, at least when it was added as a final additive. This may imply the necessity for starting the modification of UF resins with this modifier in the early steps of the resin preparation to ensure effective insertion into the network structure (Essawy et al 2009;2010;Essawy and Mohamed 2011). To enhance the water resistance of the MUF resin, these reactive PAMAMs were also used as additives to adjust the pH at the end stage instead of using sodium hydroxide, as in a previous study (Amirou et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The highly branched and three-dimensional architecture of these macromolecules have attracted considerable attention in the past few decades (Uhrich et al 1992;Frechet 1994;Inoue 2000). In addition to numerous applications in various fields such as medicine, chemistry, materials science, biology, and physics, there is interest in the use of dendrimers as modifiers for wood adhesives (Essawy et al 2009;2010;Essawy and Mohamed 2011;Zhou et al 2013;. The dendritic poly(amidoamine)s (PAMAMs) are among the most widely used dendrimers as a result of their ready commercialization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, it has been shown that hyperbranched molecules can be efficient modifiers for vinylester-urethane hybrid resin (Gryshchuk et al 2002), urea-formaldehyde resins (Essawy et al 2009), or might provide building polyurethane networks when crosslinked with isocyanates (Nasar et al 2003;Okrasa et al 2008). Having in mind that hyperbranched hydroxyl-terminated polyglycerols are highly reactive towards isocyanates, Mamiński et al (2011) recently showed that it was possible to develop fast-curing polyurethane adhesives based on hyperbranched polyglycerols.…”
Section: Introductionmentioning
confidence: 99%